Development of an international standard set of patient-centred outcome measures for overall paediatric health: a consensus process (2020)
Objective To develop an Overall Pediatric Health Standard Set (OPH-SS) of outcome measures that captures what matters to young people and their families and recognising the biopsychosocial aspects of health for all children and adolescents regardless of health condition. Design A modified Delphi process. Setting The International Consortium for Health Outcomes Measurement convened an international Working Group (WG) comprised of 23 international experts from 12 countries in the field of paediatrics, family medicine, psychometrics as well as patient advisors. The WG participated in 11 video-conferences, through a modified Delphi process and 9 surveys between March 2018 and January 2020 consensus was reached on a final recommended health outcome standard set. By a literature review conducted in March 2018, 1136 articles were screened for clinician and patient-reported or proxy-reported outcomes. Further, 4315 clinical trials and 12 paediatric health surveys were scanned. Between November 2019 and January 2020, the final standard set was endorsed by a patient validation (n=270) and a health professional (n=51) survey. Results From a total of 63 identified outcomes, consensus was formed on a standard set of outcome measures that comprises 10 patient-reported outcomes, 5 clinician-reported measures, and 6 case-mix variables. The four developmental age-specific packages (ie, 0–5, 6–12, 13–17, 18–24 years) include either five or six measures with an average time for completion of 20 min. Conclusions The OPH-SS is a starting point to drive value-based paediatric healthcare delivery from a global perspective for enhancing child and adolescent physical health and psychosocial well-being.